Analisis Hubungan Tingkat Keparahan dan Intervensi Terapi dengan Kemampuan Fungsional Anak Cerebral Palsy - Sukadarwanto Sukadarwanto; Nitaya Putri Nur Hidayati; Eka Sulistiyawati (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Cerebral palsy (CP) is a permanent neurological disorder that causes motor impairments in children, affecting their functional abilities, mobility, and social participation. Therapeutic interventions and the severity of cerebral palsy are thought to play a role in improving the functional abilities of children with CP. However, studies that comprehensively assess these factors remain limited, particularly in Indonesia. Objectives: This study was conducted to identify factors contributing to the functional abilities of children with CP using an evidence-based approach. Methods: This study employed a retrospective cohort design with multivariate analysis. Secondary data were obtained from the 2024 PPRBM database. Analysis was conducted in stages, beginning with descriptive analysis to characterize the sample, followed by bivariate analysis using the Chi-square test and General Linear Model. Results: A combination of physical therapy, occupational therapy, and speech therapy was found to be significantly associated with improved functional ability (OR = 4.3; 95% CI: 1.15–16.16). Children with mild CP showed a significant reduction in the risk of functional disability (OR = 0.0; 95% CI: 0.00–0.02; p < 0.001), while those with moderate CP also showed a significant effect (OR = 0.2; 95% CI: 0.03–0.81; p < 0.05). In the severe and moderate-to-severe CP categories, there was a trend toward a negative association, though it was not statistically significant. Conclusion: The severity of Cerebral Palsy is the most dominant and significant factor influencing the functional ability of children with CP. Keywords: Cerebral Palsy, Functional Ability, Therapy.